Penyebab Dan Solusi Cerai Gugat di Pengadilan Agama Sukoharjo - Fadhilah Umi Nur’aini; Salsabilla Bintang Maharani; Yugo Raiasa Citrasmara Noor T; Berliana Kharisma Asti; Josef Purwadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze the causes of the high number of contested divorces and to find out solutions to the high rate of contested divorces in the Sukoharjo Religious Court. This research uses empirical research. The research results show that the high rate of divorce is caused by various factors, namely: economic factors, third party factors and moral factors. These three factors are the main causes. The solution to contested divorce is to mediate with the parties and provide legal education to the community regarding the impacts of divorce